Assessment of Tribal Healthcare Infrastructure for Delivery of Maternal Health Program in Balasore District, Odisha, India - Ranjit Kumar Dehury (ACHSM, 2021)
Introduction: There are still large number of maternal deaths in India nearing up to 50,000 deaths in a year which is one sixth of the world in recent years. Odisha (India) is also not performing well in maternal health care management despite its commitment in MDG and SDG. Odisha constitute 23% of tribal population, where the maternal mortality is very high and difficult to provide health services, particularly maternal health services. The study aims to assess provision of necessary health services for pregnant women in an inaccessible tribal pockets. Methods: The study was conducted in Balasore district, Odisha (India) where a sizable population is consisting of various indigenous tribes, particularly in some blocks. The Parijata tool was used to assess various health care facilities which was developed by UNICEF and ARTH, Rajasthan. By this, availability of basic things like manpower, drugs and consumables are assessed along with laid down clinical practices and procedures. Results: The study found that there is lack of provisioning of health services in healthcare facilities. Both District hospital at Balasore and Sub-district hospitals lack basic services recommended by WHO for taking care of women. Further, the effort of government to implement a uniform program across the state hinder the tailoring of services for tribal pockets. Conclusion: The study provides remedial measures for improving the role and functioning of grass roots workers, integrating indigenous medicine with biomedicine, and revamping health information system to incorporate cultural features, thereby improving its utilization in the study area. The study raised critical issues about potential of maternal health program to deliver effective care of pregnant women in tribal dominated areas.